Modified Concrete Ability for Removing Cadmium (2) From Wastewater - Elham Asrari; Mohammad Reza Emami (EQA, 2018)
Cadmiumis found in high concentrations in industrial wastewater. In this study, using two adsorbent in concrete has been discussed. The solutions of iron nanoparticle as the first absorbent have been used in amounts of 20, 30 and 40 mg/l. The rice husk as the second adsorbent was converted to rice husk ash in 500 to 650°C. The rice husk ash mixed to 40% by weight of cement in the concrete structure. Samples, with nanoparticle, with rice husk, and combination nanoparticles and rice husk, were constructed. The samples under the different conditions such as pH, contact time, concentration of absorbent and cadmium concentrations in solution were examined. The maximum absorption 97.5% could be occurred in optimum contact time 6 hours, absorbent concentration 40 mg/l, the optimum pH 3 and wastewater concentration 10 ppm. To remove cadmium, modified concrete can be suggested as new and efficient method.